The multi-protective role of dietary betaine in largemouth bass (Micropterus salmoides): coordinating antioxidant, inflammatory, and metabolic homeostasis under high-fat diet stress - Liu, Yi-Jia; Guo, Jian; Li, Chang-Da; Han, Si-Yin; Cai, Lu (Frontiers in Physiology, 2025)
IntroductionIntensive aquaculture frequently utilizes high-fat diets (HF) as a cost-effective strategy, yet this practice often induces hepatic steatosis, oxidative stress, and chronic inflammation in carnivorous fish. Betaine, a natural methyl donor, has shown potential as a functional feed additive, but its comprehensive protective mechanisms under HF stress remain to be fully elucidated.MethodsJuvenile largemouth bass (Micropterus salmoides) were fed one of four isonitrogenous diets for 8 weeks: a normal-fat control (Control), a high-fat diet (HF), and two high-fat diets supplemented with 0.5% (HFB0.5) or 1.0% (HFB1) betaine. Growth performance, digestive enzyme activities, serum biochemical parameters, hepatic antioxidant capacity, and the expression of genes related to antioxidant defense, lipid metabolism, and inflammation were analyzed.ResultsThe HF group exhibited significantly impaired growth, digestive function, and antioxidant capacity, along with elevated lipid peroxidation, dyslipidemia, and pro-inflammatory cytokine expression. Betaine supplementation restored growth performance and feed efficiency to control levels, ameliorated digestive enzyme activities (particularly enhancing lipase), and activated the hepatic Nrf2-Keap1 pathway, upregulating antioxidant genes (nrf2, sod1, cat, gpx, ho-1, gr) and enhancing enzyme activities. Betaine also improved serum lipid profiles, upregulated genes related to fatty acid oxidation (pparα, cpt-1) and lipolysis (lpl, hsl), suppressed lipogenic genes (srebp-1, fas), and rebalanced inflammatory cytokines by reducing tnf-α and il-1β while increasing tgf-β1 and il-10.DiscussionDietary betaine effectively counteracts HF-induced metabolic stress in M. salmoides through coordinated multi-pathway regulation. It enhances antioxidant defense, reprograms hepatic lipid metabolism toward catabolism, and restores inflammatory homeostasis. These findings underscore betaine’s role as a multi-functional feed additive capable of mitigating HF-related metabolic disorders and promoting overall health in carnivorous fish aquaculture.